A Web-Based Tool for Quantification of Potential Gains in Life Expectancy by Preventing Cause-Specific Mortality - Chandran, Aruna; Xu, Churong; Gross, Jonathan; Leifheit, Kathryn M.; Phelan-Emrick, Darcy; Helleringer, Stephane; Althoff, Keri N. (Frontiers in Public Health, 2021)
Introduction: Local health departments are currently limited in their ability to use life expectancy (LE) as a benchmark for improving community health. In collaboration with the Baltimore City Health Department, our aim was to develop a web-based tool to estimate the potential lives saved and gains in LE in specific neighborhoods following interventions targeting achievable reductions in preventable deaths. Methods: The PROLONGER (ImPROved LONGEvity through Reductions in Cause-Specific Deaths) tool utilizes a novel Lives Saved Simulation model to estimate neighborhood-level potential change in LE after specified reduction in cause-specific mortality. This analysis uses 2012-2016 deaths in Baltimore City residents; a 20% reduction in heart disease mortality is shown as a case study. Results: According to PROLONGER, if heart disease deaths could be reduced by 20% in a given neighborhood in Baltimore City, there could be up to a 2.3-year increase in neighborhood LE. The neighborhoods with highest expected LE increase are not the same as those with highest heart disease mortality burden or lowest overall life expectancies. Discussion: PROLONGER is a practical resource for local health officials in prioritizing scarce resources to improve health outcomes. Focusing programs based on potential LE impact at the neighborhood level could lend new information for targeting of place-based public health interventions.